PENGARUH GRADASI AGREGAT TERHADAP DAYA DUKUNG BASE A - Sumiati Sumiati (PILAR, 2011)
The road construction with flexible pavement generally is often happened damaged. One of damage cause what  material usage  which is do not fulfill specification. Gradation fulfilling specification that is gradation following equation of Fuller or at least following the specification of aggregate of Base A (SNI 03-6388-2000). The research will use three existing sampel where sampel 1 representing dominant aggregate  have the smooth gradation , sampel 2 have harsh gradation and sampel 3 have different gradation and also compare with analogical aggregate of Fuller or specification of Base A. Result of research of physical aggregate showed: Abrasi of Aggregate 18,50%, aggregate have the character of the non plastis, Iump of clay 0% and specific gravity 2,70. Result of compaction test indicate that aggregate gradation very influence  density at aggregate with equation Fuller is  2,29 gr/cm3, successive of sample  1, sample 2 and sample 3, that is ; 2,24 gr/cm3; 2,19 gr/cm3 and 2,15 gr/cm3. Progressively lower compaction  progressively lower bearing capacity , where bearing capacity highest at aggregate with equation of Fuller: 90,63% and successive of sampel 1, sample 2 and also sampel 3  is 85,69%, 80,82% and 75,28%. Gradation of Aggregate represent one of aspect which must be paid attention to, because this matter can, preventing incidence of damage of quicker road;street from age plan.